The Effect of Repeated Whole-Body Cryotherapy on Sirt1 and Sirt3 Concentrations and Oxidative Status in Older and Young Men Performing Different Levels of Physical Activity - Gabriela Wojciak; Jadwiga Szymura; Zbigniew Szygula; Joanna Gradek; Magdalena Wiecek (MDPI AG, 2020)
Background: The activity of antioxidant enzymes and sirtuins (Sirt) decreases along with age, which is counteracted by aerobic training. Sirtuins increase antioxidant defence. Whole-body cryotherapy (WBC) increases total antioxidant capacity (TAC) in young men. The aim of our study was to assess the impact of 24 WBC treatments on the blood concentration of selected sirtuins and the level of antioxidant defence as well as oxidative stress index of training and non-training men depending on age. Methods: The study involved 40 males. In each group, there were 10 non-training older and young men (60 NTR and 20 NTR), and 10 older and young long-distance runners (60 TR, 20 TR). During an 8-week period, participants underwent 24 WBC treatments (3 min −130 °C), which were performed three times a week (Monday, Wednesday, Friday). The concentrations of Sirt1, Sirt3, TAC, total oxidative status and the activity of superoxide dismutase (SOD), catalase and glutathione peroxidase (GPx) in the blood were determined before 1 WBC and after 1 WBC, 12 WBC and 24 WBC. Results: After 1 WBC, the activity of GPx and the concentration of Sirt1 and TAC in 60 TR and TAC in 60 NTR increased. After 12 WBC, the level of Sirt1 in 20 NTR and SOD in 20 TR increased. After 24 WBC, the level of Sirt1 increased in 60 TR and in 20 NTR, Sirt3 in 60 TR and SOD in 20 TR. Conclusions: Cryogenic temperatures increase blood levels of Sirt1 and Sirt3 and systemic antioxidant defence in men, but the effect is dependent on age, level of performed physical activity and the number of applied treatments.